Reinforcement of the speaking skill in students of 9th grade by using a blog to provide audiovisual input (2021)
This document provides information related to a material design process for reinforce English speaking skills through a digital blog. This material was created for five ninth-grade students from a private school, whose main difficulty was low self-esteem, which made it difficult for them to speak English.